(untitled) (Annals of Medical Research, 2021)
Endometriosis is a chronic and enigmatic disease that affects reproductive-age women exhibiting chronic pelvic pain and infertility. The advanced stage of the disease can be diagnosed when a cystic ovarian lesion called endometrioma exists. Endometrioma is a condition that occurs when endometriotic cells invade the ovarian cortex and manifest themselves as a mass within the ovary on ultrasonography. In general, malignant transformation of ovarian endometriomas is rare, but the possibility of underlying malignancy requires individualization and caution in managing these patients. Serum tumor markers, imaging modalities, clinical conditions of the patient, and risk scoring algorithms should be taken into account for evaluating endometriotic cysts as other adnexal masses. In this rare case, we tried to present the importance of the preoperative estimation of serum HE-4 level and Risk of Malignancy Algorithm (ROMA) risk scoring index in a patient with colossal endometrioma and extremely high CA-125 and CA-19-9 levels.